2017
DOI: 10.1080/00015458.2017.1310480
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between lunar cycle and haemorrhagic complication rate in surgery

Abstract: No statistically significant correlations were found between moon cycles and postoperative haemorrhagic complications (p = .50).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 36 publications
0
2
0
1
Order By: Relevance
“…Human physiology is affected by yearly rhythms, e.g., by the lunar cycle and the seasons. The frequency of emergency presentations for reasons such as birth, sleep, rupture of abdominal aorta and intracranial aneurysm, acute coronary events, gastrointestinal bleeding, psychiatric episodes in children and adults, post-surgical bleeding and complications, stroke, epileptic and psychogenic seizures, kidney transplant results, trauma are the common cases associated with the lunar cycle ( 6 , 7 , 12 , 13 , 14 , 15 ). The belief that some parts of the body are related to some positions of the moon is expressed with “zodiacal constellations”.…”
Section: Discussionmentioning
confidence: 99%
“…Human physiology is affected by yearly rhythms, e.g., by the lunar cycle and the seasons. The frequency of emergency presentations for reasons such as birth, sleep, rupture of abdominal aorta and intracranial aneurysm, acute coronary events, gastrointestinal bleeding, psychiatric episodes in children and adults, post-surgical bleeding and complications, stroke, epileptic and psychogenic seizures, kidney transplant results, trauma are the common cases associated with the lunar cycle ( 6 , 7 , 12 , 13 , 14 , 15 ). The belief that some parts of the body are related to some positions of the moon is expressed with “zodiacal constellations”.…”
Section: Discussionmentioning
confidence: 99%
“…Doğum, uyku, abdominal aorta ve intrakraniyal anevrizma rüptürü, akut koroner olaylar, gastrointestinal kanama, çocuklarda ve yetişkinlerde psikiyatrik nedenli başvurular, cerrahi sonrası kanama ve komplikasyonlar, inme, epileptik ve psikojenik nöbet, böbrek nakli sonuçları, travma nedenli acil başvuru sıklığı, ay döngüsü ile ilişkisi araştırılan başlıca durumlardır. 3,4,[19][20][21][22][23][24][25][26][27][28][29][30] Bu çalışmaların bazılarında ay döngüsü ile hastalık sıklığı arasında ilişki tespit edilmiş olsa da pek çoğunda herhangi bir ilişki tespit edilmemiştir. Ay döngüsünün insan sağlığı üzerine etkisinde, temelde dolunay döneminde oluşan değişiklikler dikkate alınmaktadır.…”
Section: Discussionunclassified
“…t is commonly believed that the full moon affects human behavior and the occurrence and outcome of various diseases. [1][2][3][4] Previous studies have suggested that lunar phases might be associated with an increased incident risk of cardiovascular diseases such as acute myocardial infarction (AMI) 3 or atrial fibrillation. 5 These cardiovascular diseases could be the cause of out-of-hospital cardiac arrest (OHCA).…”
mentioning
confidence: 99%